2009
DOI: 10.1007/s11205-009-9528-4
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Family Correlates of Suicidal Ideation Among Chinese Adolescents in Hong Kong

Abstract: Suicidal ideation , Hopelessness, Social problem solving, Emotional competence, Family functioning, Parent-adolescent communication,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Another possible reason might be that depressed individuals have a loss of interest and feel hopeless, which is a cardinal feature that leads them to attempt suicide. Furthermore, depression may impair their decision-making capacity, which leads them to seek escape mechanisms from their stressful encounters (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason might be that depressed individuals have a loss of interest and feel hopeless, which is a cardinal feature that leads them to attempt suicide. Furthermore, depression may impair their decision-making capacity, which leads them to seek escape mechanisms from their stressful encounters (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Balazs et al (2018) suggested that HRQoL mediated the relationship between emotional and peer problems and suicidal risk. On the contrary, two other studies reported that the relationship between HRQoL and self-harm/suicidality was mediated by mental disorders or HRQoL affected self-harm/suicidality mainly through hopelessness (Gyori et al, 2021;Kwok and Shek, 2010).…”
Section: Association Between Hrqol and Self-harm/suicidalitymentioning
confidence: 91%
“…It should be noted that results on suicidal ideation were also inconsistent. While three studies showed evidence of association between suicidal ideation and overall QoL as well as family QoL (Kwok and Shek, 2010;Luo et al, 2021; Studies included for narrative synthesis (n=23) Wang et al, 2019), the study by Algorta and colleagues found no association between suicidal ideation and QoL when both family QoL and total QoL were in the same model (Algorta et al, 2011).…”
Section: Association Between Hrqol and Self-harm/suicidalitymentioning
confidence: 99%
“…The government and health agencies are increasingly focusing on mental health promotion, suicide prevention, and intervention strategies, recognizing the multi-faceted nature of suicide (Zhang et al, 2002 ). Empirical research has also been focused on suicide among specific populations, as elders (Cheng et al, 2014 ), cancer (Nigussie et al, 2023 ), mental health (Dong et al, 2019 ) or terminally – ill patients (Lam, 2007 ), survivors of child abuse (Liu et al, 2022 ), and subpopulations under specifically risks, as LGTBI+ youth (Wang et al, 2021 ), left-behind children (Xiao et al, 2019 ) or adolescents (Lai Kwok and Shek, 2010 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%